DEVELOPMENT OF COMMUNICATION IN CHILDREN - Gulchiroy, Yakubjonova; Karshiyevna, Muminova Umida (PT. Antis International Publisher, 2024)
In this article, the processes of communication and adaptation formed in people are highlighted, broad concepts of communication, the theories of scientists about the development of communication and independent thinking skills in children are cited